Progressive Colonization of Bacteria and Degradation of Rice Straw in the Rumen by Illumina Sequencing - Cheng, Yanfen; Wang, Ying; Li, Yuanfei; Zhang, Yipeng; Liu, Tianyi; Wang, Yu; Sharpton, Thomas J.; Zhu, Weiyun (Frontiers in Microbiology, 2017)
The aim of this study was to improve the utilization of rice straw as forage in ruminants by investigating the degradation pattern of rice straw in the dairy cow rumen. Ground up rice straw was incubated in situ in the rumens of three Holstein cows over a period of 72 h. The rumen fluid at 0 h and the rice straw at 0.5, 1, 2, 4, 6, 12, 24, 48, and 72 h were collected for analysis of the bacterial community and the degradation of the rice straw. The bacterial community and the carbohydrate-active enzymes in the rumen fluid were analyzed by metagenomics. The diversity of bacteria loosely and tightly attached to the rice straw was investigated by scanning electron microscopy and Miseq sequencing of 16S rRNA genes. The predominant genus in the rumen fluid was Prevotella, followed by Bacteroides, Butyrivibrio, unclassified Desulfobulbaceae, Desulfovibrio, and unclassified Sphingobacteriaceae. The main enzymes were members of the glycosyl hydrolase family, divided into four categories (cellulases, hemicellulases, debranching enzymes, and oligosaccharide-degrading enzymes), with oligosaccharide-degrading enzymes being the most abundant. No significant degradation of rice straw was observed between 0.5 and 6 h, whereas the rice straw was rapidly degraded between 6 and 24 h. The degradation then gradually slowed between 24 and 72 h. A high proportion of unclassified bacteria were attached to the rice straw and that Prevotella, Ruminococcus, and Butyrivibrio were the predominant classified genera in the loosely and tightly attached fractions. The composition of the loosely attached bacterial community remained consistent throughout the incubation, whereas a significant shift in composition was observed in the tightly attached bacterial community after 6 h of incubation. This shift resulted in a significant reduction in numbers of Bacteroidetes and a significant increase in numbers of Firmicutes. In conclusion, the degradation pattern of rice straw in the dairy cow rumen indicates a strong contribution by tightly attached bacteria, especially after 6 h incubation, but most of these bacteria were not taxonomically characterized. Thus, these bacteria should be further identified and subjected to functional analysis to improve the utilization of crop residues in ruminants.